2000
DOI: 10.1086/302844
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Heteroplasmy in the HVII Region of mtDNA Differs across Tissue Types and Increases with Age

Abstract: An immobilized sequence-specific oligonucleotide (SSO) probe system consisting of 16 SSO probes that detect sequence polymorphisms within five regions of the mtDNA control region was used to investigate the frequency of heteroplasmy in human mtDNA. Five regions of hypervariable region II (HVII) of the control region were studied in blood-, muscle-, heart-, and brain-tissue samples collected from 43 individuals during autopsy. An initial search for heteroplasmy was conducted by use of the SSO probe system. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
79
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 43 publications
7
79
1
1
Order By: Relevance
“…Before the application of next-generation sequencing (NGS) technologies, most studies focused on the mtDNA control region and revealed that 6∼11.6% of the population carry heteroplasmy in this region (9)(10)(11). The advent of NGS technologies enables the inquiry of mitochondrial heteroplasmy at the genome-wide scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Before the application of next-generation sequencing (NGS) technologies, most studies focused on the mtDNA control region and revealed that 6∼11.6% of the population carry heteroplasmy in this region (9)(10)(11). The advent of NGS technologies enables the inquiry of mitochondrial heteroplasmy at the genome-wide scale.…”
mentioning
confidence: 99%
“…It has been recognized that mitochondrial heteroplasmy across the genome increases with age (9,(18)(19)(20) and acquires unique patterns in tumors (21,22). A recent epidemiological study indicates that pathogenic mtDNA mutations might be more common in the general population than previously appreciated (23).…”
mentioning
confidence: 99%
“…The point mutations, A189G and T408A, were identified in skeletal muscle. The fibroblastspecific T414G was absent in muscle and heart in several studies (Calloway et al ., 2000;Wang et al ., 2001;Nekhaeva et al ., 2002) yet another study found T414G in muscle but not in brain (Murdock et al ., 2000). A more recent study has linked reduced COX activity to an increasing burden of multiple mtDNA point mutations, rather than a single specific point mutation, present in the genes coding for COX (Lin et al ., 2002).…”
Section: High Levels Of Mtdna Mutations Cause Diseasementioning
confidence: 88%
“…(20). This commercial kit contains more probes than previously published immobilized SSO typing assays (7,8,(23)(24)(25).…”
Section: Dna Sequencingmentioning
confidence: 99%